The impacts of fans’ attachment, sincerity and social media usage on attitude toward sports sponsorship - Yunos, Mohd Naufal; Zanuddin, Hasmah; Cheong, Jadeera Phaik Geok (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Sport communication entails a strategic mechanism in gaining an audience and loyal supporter for sportsmen fan. The objective of this article is to provide insight towards fan attachment through social media and sponsorship on mindsets about sponsor and plans to acquire products of the sponsor. Data was accumulated via survey technique. The surveys were completed by supporters. The hypothesized model was tested by a theoretical framework. The results showed that team attractiveness, team faith, and team commitment are positively linked to team affection. While team connection was observed to positively impact supporter devotion, sports enthusiasts’ Facebook use was observed to significantly strengthen their devotion and sport shoppers who see a match among the sponsor and sports team are more apt to consider that the sponsor’s intentions are genuine and honesty opinions which in turn, positively impact mindsets for sponsor and intentions to buy the sponsor’s goods. The study also offers experimental proof for the direct effects of perceived fit and supporters’ use of social media for obtaining team-related info on buy intentions. Results of the present study propose that sponsor companies should link their genuine intentions, their match with the sponsored sports team and be acive on social media accounts of the sports team in order to influence their sponsorship. This survey indicated that sports team concentrating on social media utilization has a positive impact on intentions to buy products of sponsor in an emergent market setting, in motorsports.